2021
DOI: 10.4168/aair.2021.13.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Severe Asthma: Results From Severe Asthma Network in Italy-SANI

Abstract: Purpose After adolescence, asthma is more frequent in females than in males due to different hormonal, immunologic, and occupational/environmental factors. The higher prevalence and severity of the disease in females have already been reported in international registries. The aim of this study was to explore the difference in terms of clinical, functional, and biological characteristics between male and female patients with severe asthma in a real-life, registry-based setting. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 32 publications
1
23
2
Order By: Relevance
“…Many asthma treatments are targeted towards T2 inflammation (e.g. inhaled and systemic corticosteroids and biologics targeted at IL-4, IL-5 and IL-13), which has been shown to be less common in women compared with men [97,98]. This could contribute to poorer control of asthma in women, regardless of treatment and compliance [99], and a more severe clinical manifestation or perception of asthma [100,101].…”
Section: Effectiveness Of Therapiesmentioning
confidence: 99%
“…Many asthma treatments are targeted towards T2 inflammation (e.g. inhaled and systemic corticosteroids and biologics targeted at IL-4, IL-5 and IL-13), which has been shown to be less common in women compared with men [97,98]. This could contribute to poorer control of asthma in women, regardless of treatment and compliance [99], and a more severe clinical manifestation or perception of asthma [100,101].…”
Section: Effectiveness Of Therapiesmentioning
confidence: 99%
“…The consistent message is that in cohorts of patients with asthma with high disease burden, there is invariably an excess of female patients. A report from the Severe Asthma Network in Italy registry (n=1123) found that two thirds of severe asthma patients were female and reported increased obesity and gastro-oesophageal reflux as well as increased age of onset in females [108]. Females had greater disease burden with more hospitalisations and worse asthma control while males had greater markers of T2 inflammation such as eosinophilia and IgE levels.…”
Section: Asthmamentioning
confidence: 99%
“…Interestingly, during childhood, asthma is more frequent in boys than in girls (16); then the pattern reverses around 16-18 years of age (17). In adulthood, in addition to a higher prevalence, asthma is more severe in women, who tend to have higher healthcare use, poor asthma control, and a higher number of severe exacerbations leading to hospitalization than men (18)(19)(20). In adulthood, a sex-based difference is also observed in COPD with regard to clinicoradiographic phenotype, symptom severity, and quality of life.…”
Section: Women and Men Are Not Equal In The Face Of Respiratory Diseasesmentioning
confidence: 99%